2017
DOI: 10.1177/0011128717714203
|View full text |Cite
|
Sign up to set email alerts
|

Juveniles on Trial: Mode of Conviction and the Adult Court Sentencing of Transferred Juveniles

Abstract: Several studies have compared the criminal court sentences given to transferred juveniles with those given to adults, but this research has reported inconsistent findings. In addition, some research has found that mode of conviction can interact with offenders’ characteristics, resulting in stronger or weaker effects of these factors among defendants convicted at trials. The current study explores the direct effects of juvenile status on sentence severity and whether these effects are conditioned by mode of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…The defendants' age at the time of the offense was measured continuously in the original data set, but for analytic purposes, this variable was condensed into categories. Prior sentencing research has categorized defendant age in a variety of ways, with some studies using two age groups (Franklin, 2015;Kramer & Ulmer, 2009;Warren et al, 2012), three groups (Freiburger & Hilinski, 2013;Lehmann & Gomez, 2021), four groups (Curry & Corral-Camacho, 2008;Spohn & Holleran, 2000;Steffensmeier et al, 2017), or five or more groups (Doerner & Demuth, 2010;Lehmann et al, 2018;Ryon et al, 2017). Multiple alternatives were explored, but two age groups -18-29 and 30 and over-were settled on because very few older female defendants, and especially older Black and Hispanic females, were convicted at trial.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The defendants' age at the time of the offense was measured continuously in the original data set, but for analytic purposes, this variable was condensed into categories. Prior sentencing research has categorized defendant age in a variety of ways, with some studies using two age groups (Franklin, 2015;Kramer & Ulmer, 2009;Warren et al, 2012), three groups (Freiburger & Hilinski, 2013;Lehmann & Gomez, 2021), four groups (Curry & Corral-Camacho, 2008;Spohn & Holleran, 2000;Steffensmeier et al, 2017), or five or more groups (Doerner & Demuth, 2010;Lehmann et al, 2018;Ryon et al, 2017). Multiple alternatives were explored, but two age groups -18-29 and 30 and over-were settled on because very few older female defendants, and especially older Black and Hispanic females, were convicted at trial.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Previous work on trial penalties has considered the interactive influence that mode of conviction might have on sentencing in conjunction with a variety of defendant characteristics, including race/ethnicity, gender, age, and time to conviction (e.g., Bradley-Engen et al, 2012;Holmes, 2019;Johnson, 2003;Lehmann et al, 2018). Some scholarship also has explored the moderating effects of various dimensions of case seriousness on trial-plea sentencing disparities, though how these relationships might emerge remains theoretically contradictory and empirically inconsistent.…”
Section: The Role Of Case Seriousnessmentioning
confidence: 99%
“…Specifically, while a trial conviction frequently has been found to be associated with an increased likelihood of incarceration and longer terms of imprisonment (e.g., Bushway & Piehl, 2007;Engen & Gainey, 2000;Johnson, 2006;Kim, 2015;King et al, 2005;McCoy, 2005;Steffensmeier & Demuth, 2000, 2001Ulmer & Johnson, 2004;Wooldredge, 2007) as well as a decreased likelihood of experiencing beneficial guideline departures (Engen et al, 2003;Johnson, 2005;Johnson et al, 2008), limited work has explored the offender-level circumstances under which trial-plea disparities can be more or less pronounced. Further, much of this research centers on the moderating effects of extralegal factors, including race/ethnicity (Johnson, 2003;Ulmer, 1997), gender (Holmes, 2019), age (Lehmann et al, 2018), and time to conviction (Bradley- Engen et al, 2012).…”
mentioning
confidence: 99%
“…Mental health, psychological well-being and the emotional state of adolescents awaiting court decision or serving the sentence are mediated by additional factors, such as social isolation, the lack of the possibility of independent decision-making, difficulties in adapting to the conditions of detention and the necessity to comply with formal and informal rules in the place of detention [20][21][22].…”
Section: Psychological Well-being and Emotional State In Adolescencementioning
confidence: 99%